Evidence and recommendations for a value-based decision making on vaccinations. (20th October 2021) - de Waure, C; Calabrò, GE; Tognetto, A; Carini, E; Giacchetta, I; Bonanno, E; Mariani, M; Ricciardi, W; de Waure, C
Abstract: Issue/problem: Vaccinations are one of the most successful public health measures and contribute to the achievement of Sustainable Development Goals. Despite this, there are still several challenges, such as poor resources, unequal access, and vaccine hesitancy. An exploitation of the full value of vaccinations could help contrasting them. Description of the problem: A dual approach was followed to exploit full value of vaccinations. First, the four pillars of value pinpointed by the Expert Panel on Effective Ways of Investing in Health of the European Commission, namely personal, societal, allocative, and technical value, were considered to carry out a systematic review of available papers addressing the value of vaccinations. The synthesis of data was the submitted to a panel of international experts in vaccinations who gave inputs on recommendations to drive a value-based decision-making. Results: Overall, 54 papers published from 2010 onwards addressed at least one pillar of value with most of them (83.3%) assessing a single one. Two-thirds of papers addressed the technical pillar, namely the economic value, in most cases without catching the broad economic implications. Very few studies addressed allocative and societal value highlighting the need to generate evidence to support the application of these pillars. Furthermore, some aspects of the allocative pillar, such as equity, accessibility, and appropriate use, were not addressed so far. Recommendations on research on full value of vaccinations, decision-making process and public engagement were eventually issued. Lessons: The project allowed to apply for the first the value-based approach to vaccinations. This led to the identification of current gaps in the assessment of full value of vaccinations and to recommendations to foster a value-based decision-making. These results have international relevance because of the growing attention to the value-based approach for sustainable health systems. Key messages: The full value of vaccinations need to be further investigated according to the four pillars pinpointed by the Expert Panel on Effective Ways of Investing in Health. Different actions could be promoted with respect to research, decision-making process and public engagement in order to exploit the full value of vaccination and drive a value-based decision-making.